2020
DOI: 10.1177/0300060520970765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive magnetic stimulation on motor function and GAP43 and 5-HT expression in rats with spinal cord injury

Abstract: Objectives Spinal cord injury (SCI) is a disabling central nervous system disorder. This study aimed to explore the effects of repetitive trans-spinal magnetic stimulation (rTSMS) of different spinal cord segments on movement function and growth-associated protein-43 (GAP43) and 5-hydroxytryptamine (5-HT) expression in rats after acute SCI and to preliminarily discuss the optimal rTSMS treatment site to provide a theoretical foundation and experimental evidence for clinical application of rTSMS in SCI. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Further, BMSCs exosomes treatment further enhanced the GAP-43 expression, while Shh-knockdown abolished this enhanced effect of BMSCs exosomes for GAP-43, indicating the indispensable role of Shh in the treatment for SCI using exosomes. Consistent with our results, a previous study revealed elevated GAP-43 in the spinal cord after SCI injury, and magnetic stimulation treatment further increased GAP43 level, which is beneficial to motor function recovery after acute SCI [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further, BMSCs exosomes treatment further enhanced the GAP-43 expression, while Shh-knockdown abolished this enhanced effect of BMSCs exosomes for GAP-43, indicating the indispensable role of Shh in the treatment for SCI using exosomes. Consistent with our results, a previous study revealed elevated GAP-43 in the spinal cord after SCI injury, and magnetic stimulation treatment further increased GAP43 level, which is beneficial to motor function recovery after acute SCI [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…GAP-43 is highly expressed during neuronal development and regeneration. It can mediate axon extension [ 31 ]. NF421 is a kind of neurofilament heavy polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong recently found that luteolin at a dose of 80 mg/kg protects the filtration function of the basement membrane by upregulating Nphs2 protein expression, which strikingly suppressed the apoptosis, deletion and fusion of streptozotocin-induced diabetic rat podocytes in high-glucose conditions. In addition, Xiong proposed that luteolin might inhibit glomerulosclerosis and maintain the relatively normal physiological structure of glomeruli, preventing the rapid DN-induced deterioration of the kidneys [ 74 ]. Zhang investigated the effects of luteolin on appropriated tubular injury in the kidneys of mice to explore the mechanism by which luteolin protects the kidneys in DN.…”
Section: Flavonoids For the Treatment Of Diabetic Nephropathymentioning
confidence: 99%